Capital Expansion, Employment, and Economic Stability (Book). - Snider, Joseph L. (The Accounting Review, 1940)
Reviews the book "Capital Expansion, Employment, and Economic Stability," by Harold G. Moulton, George W. Edwards, James D. Magee and Cleona Lewis.